Ionogels – materials containing immobilized ionic liquids - Andrzejewska, E.; Marcinkowska, A.; Zgrzeba, A. (Polimery, 2021)
Ionic liquids (IL) are characterized by unique properties which are the reason for the continuous growth of interest in these compounds for a large variety of applications. However, in many applications there is a need for immobilization of IL within solid matrices while maintaining IL specific properties. Such stable solid-liquid materials are called ionogels. This review provides basic information about ionogels, their preparation, properties and application with an emphasis on ionogels with polymer matrices.